P315 High symptom burden and impact on health-related quality of life in patients with Crohn's perianal fistulas: results from a global burden of illness study. (21st January 2022) - Karki, C; Sharpe, E; Hantsbarger, G; Lee, K; Perovic, M; Raven, L; Sajak-Szczerba, M; Silber, A; Yoon, A; Tozer, P
Abstract: Background: Perianal fistulas (PAF) are a common complication in Crohn's disease (CD) and can be associated with an increased burden of illness. A global study was conducted to assess the burden of illness in patients with Crohn's perianal fistulas (CPF) compared with patients with CD without PAF (non-PAF CD). Here we present patient symptom burden and impact on HRQoL. Methods: This cross-sectional study was conducted in seven countries (France, Germany, Spain, UK, Canada, Australia and Japan) in patients aged ≥21 and ≤90 years with self-reported physician-diagnosed CD. Patients were classified as having non-PAF CD (cohort, 1) or CPF without PAF-related surgery (cohort, 2) or CPF with PAF-related surgery (cohort, 3). Customised questions and validated general and disease-specific patient-reported outcome data were collected via a, 45-min IRB/EC-approved web-enabled questionnaire. Symptom burden and impact on HRQoL were evaluated using the Short Inflammatory Bowel Disease Questionnaire (SIBDQ, scores, 1–7 [low–optimum] with, 2-week recall period) in all cohorts and Quality of Life in Patients with Anal Fistula (QoLAF, scores, 14–70 [low–high impact]) in cohorts, 2 and, 3. Data were analysed using descriptive statistics. Results: Of, 929 patients recruited (cohort, 1, n=620; cohort, 2, n=174; cohort, 3, n=135), 58–69% were male and, 55–67% were aged, 21–40 years across all cohorts. Cohorts, 2 and, 3 experienced a significantly higher frequency of CD-related complications than cohort, 1 (mean [standard deviation, SD]:, 9.4 [4.5] and, 11.1 [5.2] vs, 6.0 [4.1], respectively; both p <0.05, Table, 1) and had a higher number of CD-related surgeries (other than PAF-related surgeries) in the past, 12 months (mean [SD]:, 1.8 [1.1], p =0.109 and, 2.2 [1.3], p <0.0001 vs, 1.5 [0.9], respectively). In patients with CPF, a smaller proportion in cohort, 2 had active PAF vs cohort, 3 (136 [78%] vs, 119 [88%], respectively; p =0.022) and a smaller proportion had experience with post-treatment PAF recurrence/persistence in cohort, 2 vs cohort, 3 (84 [48%] vs, 80 [59%], respectively; p =0.055). Overall SIBDQ scores were significantly lower (worse) in cohorts, 2 and, 3 than in cohort, 1 (3.8 and, 3.7 vs, 4.1 respectively; both p <0.001). In patients with CPF, total QoLAF scores were comparable between cohorts, 2 and, 3 (41 and, 42, respectively), although patients in cohort, 3 had a significantly higher (worse) score in the physical impact domain compared with cohort, 2 (21 vs, 19, respectively; p <0.05). Conclusion: In this large global study, we observed that patients with CPF had incrementally higher symptom burden, owing to both CD and PAF, compared with patients with non-PAF CD. For patients with CPF, there was no difference in HRQoL irrespective of whether they had received PAF-related surgery or not.